Sunnyside Gardens : Planning and Preservation in a Historic Garden Suburb - Kroessler, Jeffrey A (Book collections on Project MUSE., 2021)
"The first book devoted to this landmark of architecture, urban planning, and social engineering Situated in the borough of Queens, New York, Sunnyside Gardens has been an icon of urbanism and planning since its inception in the 1920s. Not the most beautifully planned community, nor the most elegant, and certainly not the most perfectly preserved, Sunnyside Gardens nevertheless endures as significant both in terms of the planning principles that inspired its creators and in its subsequent history. Why this garden suburb was built and how it has fared over its first century is at the heart of Sunnyside Gardens. Reform-minded architects and planners in England and the United States knew too well the social and environmental ills of the cities around them at the turn of the twentieth century. Garden cities gained traction across the Atlantic before the Great War, and its principles were modified by American pragmatism to fit societal conditions and applied almost as a matter of faith by urban planners for much of the twentieth century. The designers of Sunnyside- Clarence Stein, Henry Wright, Frederick Ackerman, and landscape architect Marjorie Cautley-crafted a residential community intended to foster a sense of community among residents. Richly illustrated throughout with historic and contemporary photographs as well as architectural plans of the houses, blocks, and courts, Sunnyside Gardens first explores the planning of Sunnyside, beginning with the English garden-city movement and its earliest incarnations built around London. Chapters cover the planning and building of Sunnyside and its construction by the City Housing Corporation, the design of the homes and gardens, and the tragedy of the Great Depression, when hundreds of families lost their homes. The second section examine how the garden suburbs outside London have been preserved and how aesthetic regulation is enforced in New York. The history of the preservation of Sunnyside Gardens is discussed in depth, as is the controversial proposal to place the Aluminaire House, an innovative housing prototype from the 1930s, on the only vacant site in the historic district. Sunnyside Gardens pays homage to a time when far-sighted and socially conscious architects and planners sought to build communities, not merely buildings, a spirit that has faded to near-invisibility"--